Indonesia's Tax Incentives Policies in Supporting the Post-Pandemic Trade Activities of MSMEs, Mulya Rattan - Pertiwi, Elyana Ade (Journal of Economics, Business, and Government Challenges, 2025)
This research will discuss the role of tax incentives in supporting Micro, Small, and Medium Enterprise (MSMEs), Mulya Rattan trade activity post Covid-19 Pandemic. The existence of a tax intensive program from the Indonesian government helps the export activity considering high taxes are the main problem for MSMEs. The incentive aimed to support Mulya Rattan product marketing to positively and sustainably improve their gain during economic recovery. This research is using qualitative research methods supported by primary data from in-depth interviews with the Founder of Mulya Rattan. The interviews were then analysed with existing literature studies. The result of this research shows that tax incentive issued by the Directorate General of Taxes, Ministry of Finance of the Republic of Indonesia is positive towards the MSMEs in general. However, the incentive did not make a significant difference to Mulya Rattan as the level of economic activity carried out is the same when compared to activities before the incentive was implemented. Mulya Rattan has the ability to stabilize their product export even without the help of the incentive by utilizing self-managed resources into competitive products. Therefore, if we see this phenomenon through Ambiguity-Conflict Model by Richard E. Matland, it is seen as experimental implementation. The Ambiguity of the incentive was high considering the minimal policy delivery mean utilized by the government resulting in Mulya Rattan not knowing the incentive itself.